Comparison of the Cognitive Skills of Adolescent Basketball Players and Sedentary Adolescents - Egemen Mancı; Fırat Özdalyan; Sercin Kosova; Hikmet Gümüş; Celal Gençoğlu (Selcuk University, 2021)
Starting basketball/sports at young ages, participating in practices and games for years improves children in various subjects. Chronic exercise provides a physical and physiological improvement, while also supporting cognitive development significantly. The aim of this study is to apply cognitive tests that we think reflects some cognitive skills to both athlete and sedentary adolescents compare and evaluate these test results. Twenty-two licensed male adolescent basketball players (x̄:15.59 ±.66 age) and 13 sedentary adolescents (x̄: 15.08 ±.76 age, 5 female) who did not exercise in their daily routine participated in the study. All participants were aged between 12 and 18. Three different cognitive skill tests (Mackworth Clock Test, Timewall Test, and Change Detection Test) were applied among the participants via the "Psychology Experiment Building Language Test Battery" on a laptop computer, and the results were recorded. When the findings were analyzed, the results of the Change Detection Test comparisons showed that the athletes' times of completing the whole test and their times of response to each question were shorter than those of the sedentary adolescents (both p lt;0.01). When the timing scores were analyzed according to the comparisons of the Time-Wall Test, it was seen that the athletes were significantly more successful (p lt;0.01). According to the results of the Mackworth Clock Test comparisons, the athletes' correct reaction rates and reaction times were significantly better (both p lt;0.001). In this study, some cognitive performances of the basketball player and sedentary adolescents were tested and compared to each other. Athletes are continuously exposed to a cognitive process during a practice or a game, and furthermore, they need to make a decision quickly under stress and pressure. As a result of this situation. it might be thought that adolescent athletes may have better cognitive performance than their sedentary peers since they always use these cognitive skills during practices and games for years.